Personalidad y delitos sexuales en personas privadas de la libertad de la ciudad de Loja - Castillo Castillo, Zoila Dolores (2022)
The characteristics and traits of a criminal personality are influenced by internal and external factors, as well as the way in which the individual develops within his environment, which leads to this particular behavior. The objective of this research was to determine the relationship between personality and sexual offenses in persons deprived of liberty serving their sentence in the Loja Social Rehabilitation Center (CRS - LOJA). The methodology used has a quantitative approach of non-experimental cross-sectional design, using a descriptive and correlational type of research; the population is made up of persons deprived of liberty who are sentenced for sexual crimes, which was selected by means of a non-probabilistic intentional sampling and by selection criteria. Instruments such as the Millon-III Multiaxial Clinical Inventory and a data collection form were used to determine the penal status of this population. The results identify that the most prominent personalities are: paranoid, avoidant and dependent; and that the most prevalent sexual crime committed within this population is rape, sexual abuse and sexual harassment, in the same way it is important to mention that there is no statistically significant relationship between the two study variables. Finally, these results allowed the design of a psychotherapeutic intervention proposal aimed at making personality traits more flexible and improving social skills in this population